2018
DOI: 10.3758/s13421-018-0849-x
|View full text |Cite
|
Sign up to set email alerts
|

Hey buddy, why don’t we take it outside: An experience sampling study of prospective memory

Abstract: Relatively little research has focused on how prospective memory (PM) operates outside of the laboratory, partially due to the methodological problems presented by naturalistic memory research in general and by the unique challenges of PM in particular. Experience sampling methods (ESM) offer a fruitful avenue for this type of research, as recent work from Gardner and Ascoli (Psychology and Aging, 30, 209-219, 2015) has shown. They found that people thought about PM around 15% of the time, and that future thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 54 publications
4
33
0
Order By: Relevance
“…Mental time travel is of course not limited to the past; in fact, we may spend more time thinking about the future than the past in our daily life (F. T. Anderson & McDaniel, 2019;. Prospection allows us to consider potential future scenarios (e.g., to evaluate opportunities and threats, to envision different courses of action, and to anticipate their consequences), which plays an important role in guiding many aspects of cognition and behavior, including decision-making (Bulley et al, 2016), planning and goal-directed actions (Bulley & Irish, 2018), emotion regulation (Jing et al, 2016), creativity (Addis et al, 2016), and empathy (Gaesser & Schacter, 2014).…”
Section: Representations Of the Personal Futurementioning
confidence: 99%
“…Mental time travel is of course not limited to the past; in fact, we may spend more time thinking about the future than the past in our daily life (F. T. Anderson & McDaniel, 2019;. Prospection allows us to consider potential future scenarios (e.g., to evaluate opportunities and threats, to envision different courses of action, and to anticipate their consequences), which plays an important role in guiding many aspects of cognition and behavior, including decision-making (Bulley et al, 2016), planning and goal-directed actions (Bulley & Irish, 2018), emotion regulation (Jing et al, 2016), creativity (Addis et al, 2016), and empathy (Gaesser & Schacter, 2014).…”
Section: Representations Of the Personal Futurementioning
confidence: 99%
“…This could suggest that despite their spontaneous nature, the appearance of future thoughts in participants' minds is a more resource-demanding process than the spontaneous retrieval of past events. However, when spontaneous future thoughts were separated into thoughts about future plans and imaginary future scenarios (see also Anderson & McDaniel, 2019, Plimpton et al, 2015, Warden et al, 2019, who used a similar coding scheme to categorise the content of spontaneous future thoughts), the results showed that the detrimental effect of perceptual load manipulation on future thoughts was mainly due to a markedly stronger reduction in the number of reported future scenarios than future plans. This novel finding demonstrates the importance of distinguishing different types of spontaneous future thoughts, and raises an interesting possibility that spontaneous thoughts about upcoming plans may be less constructive and more similar to involuntary autobiographical memories (i.e., their representations are already formed and get simply re-activated by incidental cues in the environment).…”
Section: Underlying Cognitive Mechanismsmentioning
confidence: 99%
“…Finally, although researchers have interrogated several aspects of this phenomenon (e.g., individual differences, priming effects), little is still understood about its content as it is rarely measured or analysed (but see Anderson & McDaniel, 2019;Mazzoni, 2019;Plimpton et al, 2015;Warden et al, 2019, for exceptions). It is interesting that when Plimpton et al (2015) carried out a thematic content analysis of task-unrelated spontaneous thoughts, reported by participants in response to thought probes during the vigilance task, they found that the majority of thoughts could be classified into two main categories of intended actions/plans and upcoming events, with a very small proportion of thoughts referring to the category of simulated hypothetical events.…”
Section: The 'Why' Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is growing evidence to show that involuntary and voluntary future thoughts are often goal-oriented, which has resulted in the use of a new term ‘autobiographical planning’ in the literature (e.g., Baird, Smallwood, & Schooler, 2011 ; Spreng, Gerlach, Turner, & Schacter, 2015 ). A recent study by Cole & Berntsen ( 2016 ) showed that IFTs were more likely to reflect people’s current concerns and goals than memories about the past (see also Anderson & McDaniel, 2018 ; Plimpton et al, 2015 ). Therefore, the occurrence of IFTs could be even more dependent on the malfunctioning of the inhibitory control mechanism specified by the self-memory system than the retrieval of IAMs.…”
Section: Role Of Cognitive Inhibition In Experiencing Involuntary Menmentioning
confidence: 99%